Webinar: Launch of an evidence synthesis of gender norms in agrifood systems: Pathways towards improved women’s economic resilience to climate change - Rietveld, Anne M.; Farnworth, Cathy Rozel; Shijagurumayum, Maghajit; Meentzen, Angela; Voss, Rachel; Morahan, Rebecca; Lopez, Diana E. (CGIAR Initiative on Gender Equality, 2024)
The webinar hosted on April 4 by ILRI for the CGIAR Gender Equality initiative, HER+ unveiled key findings and recommendations from the "An evidence synthesis of gender norms in agrifood systems: Pathways towards improved women’s economic resilience to climate change" report. The report identifies 15 gender norms that affect women’s economic resilience in agrifood systems, proposing an Economic Resilience Pathway Framework for research and action. The framework offers insights for policymakers and practitioners aiming to strengthen women’s economic resilience in agrifood systems amid climate change.